2014
DOI: 10.1128/jb.01258-13
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Transposon Insertion in phzF2 on the Specialized Metabolite Production and Interkingdom Interactions of Pseudomonas aeruginosa

Abstract: fIn microbiology, gene disruption and subsequent experiments often center on phenotypic changes caused by one class of specialized metabolites (quorum sensors, virulence factors, or natural products), disregarding global downstream metabolic effects. With the recent development of mass spectrometry-based methods and technologies for microbial metabolomics investigations, it is now possible to visualize global production of diverse classes of microbial specialized metabolites simultaneously. Using imaging mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 55 publications
2
37
0
Order By: Relevance
“…As shown in Figure 1a wide variety of specialized metabolites were detected including the phenazines pyocyanin (PYO), phenazine-1-carboxamide (PCN) and phenazine-1-carboxylic acid (PCA); quinolones 2-heptyl-4-quinolone (HHQ), PQS, 4-hydroxy-2-heptylquinoline- N -oxide (HQNO), 2-nonyl-4-quinolone (NHQ) and 2-nonenyl-hydroxy-4-quinolone (C9:db PQS) and 4-hydroxy-2-nonenylquinoline- N -oxide (C9:db NQNO) among others; various rhamnolipids as exemplified by 3-[3-[(2R,3R,4R,5R,6S)-4,5-dihydroxy-6-methyl-3-[(2S,3R,4R,5R,6S)-3,4,5-trihydroxy-6-methyloxan-2-yl]oxyoxan-2-yl]oxydecanoyloxy]decanoic acid (Rha-Rha-C10-C10) and the siderophores pyochelin and pyoverdine. [20, 21]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 1a wide variety of specialized metabolites were detected including the phenazines pyocyanin (PYO), phenazine-1-carboxamide (PCN) and phenazine-1-carboxylic acid (PCA); quinolones 2-heptyl-4-quinolone (HHQ), PQS, 4-hydroxy-2-heptylquinoline- N -oxide (HQNO), 2-nonyl-4-quinolone (NHQ) and 2-nonenyl-hydroxy-4-quinolone (C9:db PQS) and 4-hydroxy-2-nonenylquinoline- N -oxide (C9:db NQNO) among others; various rhamnolipids as exemplified by 3-[3-[(2R,3R,4R,5R,6S)-4,5-dihydroxy-6-methyl-3-[(2S,3R,4R,5R,6S)-3,4,5-trihydroxy-6-methyloxan-2-yl]oxyoxan-2-yl]oxydecanoyloxy]decanoic acid (Rha-Rha-C10-C10) and the siderophores pyochelin and pyoverdine. [20, 21]…”
Section: Resultsmentioning
confidence: 99%
“…Structural verification of ions putatively identified in IMS was performed manually by comparing the exact mass from the LC-MS/MS data and the corresponding MS/MS spectra with previously reported structural characterization. [20, 21] LC-MS/MS data analysis was performed using Bruker Daltronics DataAnalysis v4.1 (Build 362.7). Lock mass internal calibration using hexakis(1H,1H,3H-tetrafluoropropoxy)phosphazene ions (Synquest Laboratories; m/z 922.0098) was applied.…”
Section: Methodsmentioning
confidence: 99%
“…The bacterial-fungal interplay is more complex than just molecules produced by Pa , as recent elegant work has shown that Af can transform Pa metabolites, and thus radically alter the effect on the interaction, including the degree of inhibition [ 65 ]. Finally, Fe limitation by Pa could also in part be a result of modulation of Af siderophore production by Pa metabolites [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…S10C). Chemically synthesized 5-Me-PCA and the 5-Me-PCA analog PMS are yellow (52), and PMS takes on a bright green color upon reduction (53). Accumulation of a reduced form of 5-Me-PCA could occur under the reducing conditions prevailing in the highcell density, oxygen-limited conditions of stationary phase cultures; if reduced 5-Me-PCA is green, this could account for the coloration of ΔphzHS cultures.…”
Section: Mexghi-opmd Contributes To Fitness In Shaken Liquid Culturesmentioning
confidence: 99%